Towards User-Centric Transport in Europe Challenges, Solutions and Collaborations - Müller, Beate; Meyer, Gereon (Lecture Notes in Mobility, 2019)
In order to build a sustainable transport system for people and goods that meets the needs of all users, a truly integrated and seamless approach is needed, and the full potential of transformative technologies has to be exploited. This can only be achieved if user-centeredness, cross-modality and technology transfer become the paradigm of shaping future transport. Mobility4EU is a project funded by the European Commission that focusses on these topics and is working on delivering an action plan towards a user-centric and cross-modal European transport system in 2030. The authors of this contributed volume are dedicated scholars and practitioners connected to Mobility4EU either as partners or external contributors. Their contributions focus on understanding user needs and report on technologies and approaches that support the tailoring of a user-centered cross-modal transport system for passengers and freight on long distances and in the urban context.